Endoscopic ultrasound versus magnetic resonance cholangiopancreatography for the diagnosis of computed tomography‐negative common bile duct stone: Prospective randomized controlled trial. Issue 5 (12th December 2021) - Suzuki, Masato; Sekino, Yusuke; Hosono, Kunihiro; Yamamoto, Kouji; Kawana, Kenichi; Nagase, Hajime; Kubota, Kensuke; Nakajima, Atsushi
Abstract : Objectives: For suspected common bile duct stone (CBDS) missed on computed tomography (CT), there is no clear evidence on whether endoscopic ultrasound (EUS) or magnetic resonance cholangiopancreatography (MRCP) is the better diagnostic tool. We aimed to compare the diagnostic accuracy of EUS and MRCP for cases of missed CBDS on CT. Methods: Patients suspected of having CBDS were enrolled and randomly allocated to the EUS or MRCP group. Upon the initial examination, those having CBDS or sludge formation underwent endoscopic retrograde cholangiopancreatography (ERCP), while those who were CBDS‐negative underwent a second examination with either MRCP or EUS, which was distinct from the initial diagnostic procedure. The primary outcome was diagnostic accuracy, and the secondary outcomes were diagnostic ability, detection rate and characteristics of CBDS in the second examination, and the frequency of adverse events. Results: Between April 2019 and January 2021, 50 patients were enrolled in the study. The accuracy was 92.3% for EUS and 68.4% for MRCP ( P  = 0.055). EUS showed 100% sensitivity, 88.2% specificity, 81.8% positive predictive value, and 100% negative predictive value, and MRCP showed 33.3% sensitivity, 84.6% specificity, 50% positive predictive value, and 73.3% negative predictive value. The CBDS detection rate in the second examination was 0% for MRCP after a negative EUS and 35.7% for EUS after a negative MRCP ( P  = 0.041). No adverse events occurred in any of the patients. Conclusions: Endoscopic ultrasound may be a superior diagnostic tool compared to MRCP for the detection of CBDS that are undetected on CT. (UMIN000036357).